Phytochemical Screening, Antioxidant, Antidiabetic Activity, and Toxicity of Melastoma malabathricum L. Leaves - Lia Meilawati; Megawati Megawati; Indah Dwiatmi Dewijanti; Mamay Maslahat (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Extraction and fractionation have been carried out to determine the content of compounds in Harendong (Melastoma malabathricum L.) leaves, antioxidant test using the 1,1-diphenyl-2-picrylhydrazil (DPPH) method, antidiabetic using α-glucosidase enzyme, and toxicity using the Bhrine Lethality Test Shrimp method (BSLT). The study showed that the methanol extract and the ethyl acetate fraction of M. malabathricum  leaves had secondary metabolites: flavonoids, tannins, and saponins. In contrast, the butanol fraction contained flavonoids and saponins, and the water fraction contained tannins. The hexane fraction of M. malabathricum leaves did not contain secondary metabolites. The result of antioxidant and antidiabetic activity tests showed that ethyl acetate fraction has higher activity with IC50 values of  23.08 µg/mL and 3.835 µg/mL. Meanwhile, the BSLT toxicity test of methanol extract and all fractions of M. malabathricum  leaves against Artemia salina L. larva had an LC50 > 1000 g/mL.